Sequential consumption of sauce- and elegant-flavor baijiu enhances post-drinking comfort: a randomized crossover study in Guangdong, China - Yu Fu; Jianan Liu; Guoliang He; Shaohui Fan; Deliang Wang; Cheng Wang (Applied Food Research, 2025)
Baijiu, a traditional Chinese distilled spirit, exhibits diverse flavor profiles that may influence post-drinking comfort. We tested whether consuming sauce‐flavor baijiu followed by elegant-flavor baijiu enhances physiological, cognitive, and emotional outcomes versus two servings of sauce‐flavor baijiu.In a randomized, matched crossover design, 43 healthy adults underwent two sessions, each separated by a one‐week washout. In one session, participants drank two sauce‐flavor servings (53% vol); in the other, sauce‐flavor was followed by elegant‐flavor (53% vol). One hour post‐consumption and the following morning, we measured breath alcohol concentration (BrAC), Stroop task performance (reaction time and accuracy), EEG-derived attention and meditation indices, and self-reported positive/negative affect. Repeated‐measures ANCOVA, adjusting for alcohol dose and sequence, assessed condition effects.Sauce-flavor followed by elegant-flavor baijiu yielded lower BrAC at all intervals (p < 0.01), faster Stroop reaction times (p = 0.041), higher accuracy (p = 0.004), and elevated meditation scores (p = 0.031). Positive affect was greater at both time points (p < 0.01), with no change in negative affect.Sequential consumption of sauce-flavor followed by elegant-flavor baijiu appears to accelerate alcohol elimination, enhance executive function, and promote positive emotional recovery. These findings suggest that baijiu type and order can meaningfully shape the drinking experience. Future studies should elucidate underlying mechanisms and assess generalizability across broader populations.